The effects of residual organic solvent on epoxy: modeling of kinetic parameters by DSC and Borchardt-Daniels method - Rodrigues,Victor de Carvalho (2021)
Abstract The curing reactions of epoxy resins are a complex process that defines thermosets final properties and are affected by any additive present on its formulation. Considering this, the aim of this study was to analyze the influence of the solvent addition on the curing kinetics of an epoxy system. The epoxy samples were prepared using different percentages by weight of acetone: 0, 2, 5 and 10 wt.%. From DSC and DMA tests, followed by the Borchardt-Daniels kinetic analysis it was reported that the addition of acetone can decrease the reactions rate, activation energy, Tg and elastic modulus. The presence of solvent, even in small amounts, can affect the curing mechanisms of epoxy resins. The changes on the curing behavior and the low quality of the final properties for the sample with 10 wt.% of solvent indicates that this may be a limit for acetone addition on the epoxy formulations.